2019
DOI: 10.1155/2019/5921703
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Burnout and Mental-Illness-Related Stigma among Nonprofessional Occupational Mental Health Staff

Abstract: Background Stigma related to mental illness can be an obstacle affecting the quality of life of people with mental illness. Although mental illness in the workplace is a public problem globally, few studies have investigated the effect of stigma on job-related problems such as burnout. Aim This study aimed to clarify the association between mental-illness-related stigma and burnout among nonprofessional occupational mental health staff. Methods In this cross-sectional study, nonprofessional occupational mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Previous studies have found that mental illness-related stigma may cause people to increase social distance from individuals with mental illness (Link et al, 1999). In Mitake et al’s (2019) study, mental illness stigma was associated with DP. Our results are consistent with the notion that if you socially distance yourself from individuals with SMI, you are less likely to endorse cynical or negative thoughts toward them.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previous studies have found that mental illness-related stigma may cause people to increase social distance from individuals with mental illness (Link et al, 1999). In Mitake et al’s (2019) study, mental illness stigma was associated with DP. Our results are consistent with the notion that if you socially distance yourself from individuals with SMI, you are less likely to endorse cynical or negative thoughts toward them.…”
Section: Discussionmentioning
confidence: 79%
“…Without this knowledge, they may endorse stigmatized views, which may in turn lead to ineffective service delivery and increased feelings of burnout (Eno Louden, 2009). Mitake et al (2019) study found mental illness stigma was related to the DP dimension of burnout among non-professionals.…”
Section: Introductionmentioning
confidence: 85%
“…For example, Dyrbye et al (2015) showed that in medical students increased perceptions of general mental health stigma correspond to greater burnout symptomology whereas Mullen and Crowe (2017) report a small negative correlation between these constructs in school counselors. Also, in sample of occupational mental health non-professionals residing in Japan, Mitake et al (2019) found inconsistent relationships between burnout and perceived mental-illness-related stigma. Although investigating self -stigma and not perceived mental-illness-related stigma, a comparative study of Lithuanian and USA non-medical mental health care providers demonstrated that global MBI scores were linked to self-stigma of seeking help, but only in the Lithuanian sample (Endriulaitienė et al, 2019).…”
Section: Studymentioning
confidence: 97%
“…At present, qualitative studies on the impact of occupational stigma on the physical and mental health and well-being of nurses have been conducted by most researchers. 23 , 24 Only a few studies have adopted quantitative studies, and the lack of scientific instruments for assessment is one of the obstacles. So far, only part of the contents of several scales have involved occupational stigma toward nurses.…”
Section: Introductionmentioning
confidence: 99%